2020
DOI: 10.1177/0271678x20935274
|View full text |Cite
|
Sign up to set email alerts
|

Altered coupling of cerebral blood flow and functional connectivity strength in visual and higher order cognitive cortices in primary open angle glaucoma

Abstract: Primary open-angle glaucoma (POAG) has been suggested to be a neurodegenerative disease associated with altered cerebral vascular hemodynamics and widespread disruption of neuronal activity within the visual, working memory, attention and executive networks. We hypothesized that disturbed neurovascular coupling in visual and higher order cognitive cortices exists in POAG patients and correlates with glaucoma stage and visual field defects. Through multimodal magnetic resonance imaging, we evaluated the cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 65 publications
6
34
0
Order By: Relevance
“…In addition, the LG is believed to be involved in encoding visual memories (Roland and Gulyás, 1995). The decreased FC in the bilateral LG within the occipital visual network suggested trans-synaptic degeneration of the visual pathway between the primary visual cortex and higher visual cortex, which was consistent with previous studies (Dai et al, 2014;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the LG is believed to be involved in encoding visual memories (Roland and Gulyás, 1995). The decreased FC in the bilateral LG within the occipital visual network suggested trans-synaptic degeneration of the visual pathway between the primary visual cortex and higher visual cortex, which was consistent with previous studies (Dai et al, 2014;Wang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Combined ASL and fMRI, previous studies have demonstrated a striking correlation between resting-state FCS and CBF in the normal brain ( 30 , 34 ), further supporting the hypothesis of neurovascular coupling. Moreover, abnormal global and characteristic regional CBF–FCS coupling has been identified in several neuropsychiatric diseases, including schizophrenia, Wilson's disease, primary open-angle glaucoma, and generalized anxiety disorder ( 34 37 ). However, the relationship between CBF and FCS in subjects with different WMH loads remains unknown, which may provide complementary evidence for clarifying potential functional mechanisms in WMH.…”
Section: Introductionmentioning
confidence: 99%
“… 59 Alongside these various morphological alterations there were also modifications in brain activity: through the use of fMRI a reduction in the activation of the primary visual cortex following visual stimulation has been identified in POAG, 48 , 55 , 59 , 76–81 NTG 48 , 78 , 81 and PACG. 82 Using rs-fMRI, and measuring cerebral blood flow by arterial spin labeling MRI, 83 , 84 a reduction in neuronal activity was also observed in resting state in visual cortex, motor cortex, somatosensory cortex and Default Mode Network (DMN, a major neuronal network comprising prefrontal cortex, medial temporal lobe, inferior parietal lobe, posterior cingulate cortex, angular gyrus and hippocampus, that deactivates during goal-directed tasks). Neuronal connectivity in resting-state 61 , 84–86 was also found to be decreased bilaterally, both in areas directly related to the visual process (primary visual cortex and superior visual areas) and indirectly, such as between visual cortex and R superior/inferior temporal gyrus, R/L fusiform gyrus, L inferior frontal gyrus, L middle occipital gyrus, R angular gyrus, R superior occipital gyrus, L postcentral gyrus, R precentral gyrus, anterior lobe of the left cerebellum.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, increased connectivity was present towards L cerebellum, R middle cerebellar peduncle, R middle frontal gyrus and extra-nuclear gyrus. This reduction in functional connectivity appears to correlate with visual field deficit and glaucoma stage, 84 although a demonstrated cause-effect relationship is lacking to date; 85 the reduced connectivity involving visual areas has also been related with thickness reduction of retinal RNFL. 61 The reason for all these modifications is not clear; it has been suggested that the reduced functional activity and connectivity may be secondary to transsynaptic degeneration and/or decreased visual information flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation